ANALISIS PENGARUH KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Yosi Dwi Heryan; Zaenal Alim Adiwijaya (Jurnal Akuntansi Indonesia, 2013)
The purpose of this research is to investigate and get empirical about auditor big four, auditor industry specialist, and size in the earning management limit by the firms audited for IPO firms. Earning management on this research is use discretionary accrual. Audit quality on this research is used by auditor big four and auditor industry specialist. Size on this research is measured by total assets. The object of this research is non finance firms which do IPO (Initial Public Offerings) in Indonesia. It used 47 Indonesia IPO firms from 2008-2011. The method of data collection is purposive sampling method. Multiple regression is used to analysis data and develops the theory model. The result of this research indicates that auditor big four proved cannot limit the earning management for firms which is audited by auditor big four when firms do IPO. Auditor industry specialist can limit the earning management when firms do IPO in Indonesia. Size cannot limit the earning management when the firms do IPO in Indonesia